Hak dan Kewajiban Umat Beriman Kristiani Awam Menurut Kitab Hukum Kanonik Kanon 225-226 - Blasius Superma Yese; Priska Hura (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Lay Christian believers are members of the Church who have been united through the sacrament of baptism and are called to take an active part in the life of the Church. Their role is reflected in their participation in Christ's threefold mission: as prophets who proclaim the faith, as priests who participate in the sanctification effort, and as kings who serve others with a spirit of loving service. This thesis specifically examines the rights and obligations of lay people as regulated in the Code of Canon Law, particularly canons 225–226, which emphasize their responsibility in realizing the Church's mission in the world. These rights and obligations form the basis for lay people to play a role in building the mystical body of Christ, while also expanding the proclamation of the Gospel Good News so that more people can experience the grace of salvation. This research uses a literature review method by referring to various theoretical sources, including Church documents, books, scientific journals, and other relevant literature, to gain a comprehensive understanding of the position, role, and contribution of lay people in the dynamics of contemporary Church life.